High cover of forest increases the abundance of most grassland butterflies in boreal farmland. Issue 4 (29th March 2017) - Toivonen, Marjaana; Peltonen, Aino; Herzon, Irina; Heliölä, Janne; Leikola, Niko; Kuussaari, Mikko
Abstract: High cover of forest in the landscape matrix has been shown to weaken the negative effects of habitat fragmentation on grassland butterflies. No studies have however focused on examining species‐specific responses of grassland butterflies to forest. The data from 3 years of butterfly monitoring in Southern Finland were used to test whether the amount of forest cover in the surrounding landscape affected the abundance of grassland butterfly species in semi‐natural grasslands, field margins, and forest edges. More than half of the studied species benefitted from high cover of forest. Species with the strongest preference for forested landscapes were Lycaena virgaureae, Argynnis adippe, Argynnis aglaja, and Boloria selene, which probably find suitable resources in herbaceous habitats at forest edges and clearings. Several small‐sized species were positively affected by surrounding forest cover in field margins but not in the other habitat types. Although field margins are suboptimal habitats for grassland butterflies, they provide important corridors for dispersal. High cover of forest in the landscape matrix may enhance butterfly dispersal along field margins by reducing windiness, which is likely to be most important for small‐sized species with poor dispersal capacity. The most abundant grassland species showed little or no preference for forested landscapes. Our results suggest that high cover of forest enhances the persistence of most grassland butterflies, including declining species, in boreal agricultural landscapes. The responses to forest are however strongly dependent on species‐specific properties and habitat types.